Broad-Based Black Economic Empowerment & the Preferential Procurement Policy Framework Act in Selected Small and Medium Enterprises in Cape Town, South Africa - Abraham Alexander Cader; Zivanayi Mazhazha-Nyandoro (Contemporary Research in Business, Management and Economics Vol. 7, 2024)
The Broad-Based Black Economic Empowerment (BBBEE) legislation, introduced in South Africa post-1994, aims to redress economic disparities and ensure inclusive participation in the economy. Despite its noble intentions, its implementation has faced challenges, particularly for Small and Medium Enterprises (SMEs). This study explores the perceptions of SME owners and managers in Cape Town, South Africa regarding the impact of BBBEE legislation on their businesses. The findings reveal that the legislation has been more of a hindrance than a facilitator, with issues such as limited access to public sector opportunities, ’fronting’ by connected elites, and prevalent fraud and corruption. The Preferential Procurement Policy Framework Act (PPPFA), enacted to regulate public sector procurement processes, plays a crucial role in supporting BBBEE objectives. By promoting equity, transparency, and competitiveness in government procurement, the PPPFA aims to level the playing field for historically disadvantaged individuals and businesses. This study suggests that while the PPPFA has the potential to bolster BBBEE, its effectiveness is contingent on overcoming the existing challenges in the implementation of BBBEE legislation. The recommendations call for an overhaul of the legislation to ensure it effectively delivers economic empowerment to previously disadvantaged individuals and communities in South Africa.